2004
DOI: 10.1097/01.brs.0000145412.93407.c3
|View full text |Cite
|
Sign up to set email alerts
|

Results of Surgical Treatment for Degenerative Cervical Myelopathy

Abstract: Anterior decompression provides good neurologic recovery in patients with degenerative cervical myelopathy. TMC provides good structural support, and solid fusion can be achieved with TMC and anterior plate (for < or =2-level corpectomy) and/or posterior plate (> or =3-level corpectomy). There is increased risk of C5 nerve root injury when first laminectomy and posterolateral plate stabilization are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…Oppositively, cervical lordosis is difficult to be reconstructed effectively using large cages or grafts in case of multilevel corpectoEur Spine J (2007) 16:2055-2071 2065 mies, because of the rectangular shape of most current devices or the design of the grafts [6,48,70]. Mean correction in patients with 2-and 3-level corpectomies was 6.8°in our series, resembling a similar value compared to other series [48,52,103], and mainly representing the lordotic shape of currently used ACPs (Fig. 7b).…”
Section: Influence Of Cervical Lordosissupporting
confidence: 77%
See 2 more Smart Citations
“…Oppositively, cervical lordosis is difficult to be reconstructed effectively using large cages or grafts in case of multilevel corpectoEur Spine J (2007) 16:2055-2071 2065 mies, because of the rectangular shape of most current devices or the design of the grafts [6,48,70]. Mean correction in patients with 2-and 3-level corpectomies was 6.8°in our series, resembling a similar value compared to other series [48,52,103], and mainly representing the lordotic shape of currently used ACPs (Fig. 7b).…”
Section: Influence Of Cervical Lordosissupporting
confidence: 77%
“…There is the potential for a higher rate of infection, surgical morbidity and increased inhospital stay. Posterior dissection can cause significant myofascial pain due to the stripping of the musculature from the posterior elements and axial neck pain [5,18,52,85,89,103,110,119]. Two of our three cases sustaining posterior fusion depicted severe and moderate posterior neck pain, respectively.…”
Section: Clinical Failures In Multilevel Anterior Cervical Constructsmentioning
confidence: 79%
See 1 more Smart Citation
“…Multilevel anterior discectomy and fusion is an alternative surgical method but it may be hard and dangerous when the disc height is greatly reduced. Recently anterior cervical corpectomy has been introduced for the treatment of patients with multilevel degenerative cervical myelopathy [2,3]. Several studies reported that anterior cervical corpectomy and fusion was an affective procedure with a more favorable neurological improvement when compared to posterior decompressive laminectomy or laminoplasty [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of surgical relatedbecause of the complicated pathological changes of the spine and the increased presence of comorbidities. Recently anterior cervical corpectomy, titanium mesh cage (TMC) supporting and anterior cervical plate fixation has become a widely used surgical procedure for the treatment of multilevel cervical spondylotic myelopathy [2][3][4]. It has also been regarded as a safe procedure even in the elderly population [4].…”
mentioning
confidence: 99%